The Urinary Glucose Excretion by Sodium–Glucose Cotransporter 2 Inhibitor in Patients With Different Levels of Renal Function: A Systematic Review and Meta-Analysis - Hu, Suiyuan; Lin, Chu; Cai, Xiaoling; Zhu, Xingyun; Lv, Fang; Nie, Lin; Ji, Linong (Frontiers in Endocrinology, 2022)
Objective Previous evidence suggested sodium glucose cotransporter 2 inhibitor (SGLT2i)-mediated urinary glucose excretion (UGE) appeared to be reduced with the decrease in glomerular filtration rate. Thus, we conducted a systematic review and meta‐analysis to compare SGLT2i-mediated UGE among individuals with different levels of renal function. Methods We conducted systematic searches in PubMed, Medline, Embase, Cochrane Central Register of Controlled Trials and ClinicalTrial.gov from inception to May 2021. Clinical studies of SGLT2i with reports of UGE changes in predefined different levels of renal function were included. The results were expressed as pooled effect sizes with 95% confidence interval (CI). Random-effects model was used to calculate the pooled effect sizes. Results In total, eight eligible studies were included. Significant differences were observed in the post-treatment UGE level among subgroups stratified by renal function (P<0.001 for subgroup difference), which were gradually decreased along with the severity of impaired renal function. Consistently, changes in UGE before and after SGLT2i treatment were also decreased along with the severity of impaired renal function [67.52 g/d (95% CI, 55.58 to 79.47 g/d) for the individuals with normal renal function; 52.41 g/d (95% CI, 38.83 to 65.99 g/d) for individuals with mild renal function impairment; 35.11 g/d (95% CI, 19.79 to 50.43 g/d) for the individuals with moderate renal function impairment; 13.53 g/d (95% CI, 7.20 to 19.86 g/d) for individuals with severe renal function impairment groups; P<0.001 for subgroup differences]. Conclusions SGLT2i-mediated UGE was renal function-dependent, which was decreased with the extent of renal function impairment.